O corpo em novas cartas portuguesas : uma análise sobre a reivindicação e a subversão da imagem da mulher - Sayão, Verônica Farias (2024)
Corporeality is a term revisited throughout human history because it is a concept constructed in society. Thus, the ideals of the body change with culture and are updated by the prevailing thought. However, the body, studied in its historicity, privileged the male physical type as superior to the female, constructing a narrative that marginalized, manipulated, and established the female body as fragile and submissive. Considering these issues, this study seeks to bring a new paradigm to female corporeality in order to investigate the body as a receptacle for socially, culturally, and historically constructed symbols and meanings. Consequently, the goal of this work is to analyse the female bodies present in the work "Novas cartas portuguesas", by Maria Isabel Barreno, Maria Velho da Costa and Maria Teresa Horta (2021), to confirm the duality between the symbolism of enclosure and the restitution associated with the female body. In other words, the focus of this research is to look for evidence that reveals this dual process in the woman's body, so as to answer how the representation of the female body in the work serves as a lever for the identity and humanitarian reclaiming of women within the context of the Portuguese dictatorship. To achieve this, the methodology employed includes a historical analysis of the body in the West and how it has been constructed up to the present day, in order to expose how concepts are modular within the dominant narrative. Next, I seek to outline the context of the Portuguese military dictatorship and its rhetorical mechanism as a guiding principle for bodies in terms of docility-utility. Finally, I analyse selected fragments of the work to delineate how the construction of an enclosure-body and a weapon-body takes place, terms coined here with the intention of highlighting the oppressive and liberating processes that Portuguese women experienced within the context of the Estado Novo.